Two-Grid Method for Burgers’ Equation by a New Mixed Finite Element Scheme - Hu, Xiaohui; Huang, Pengzhan; Feng, Xinlong (Mathematical Modelling and Analysis, 2014)
In this article, we present two-grid stable mixed finite element method for the 2D Burgers’ equation approximated by the -P1 pair which satisfies the inf–sup condition. This method consists in dealing with the nonlinear system on a coarse mesh with width H and the linear system on a fine mesh with width h << H by using Crank–Nicolson time-discretization scheme. Our results show that if we choose H2 = h this method can achieve asymptotically optimal approximation. Error estimates are derived in detail. Finally, numerical experiments show the efficiency of our proposed method and justify the theoretical results.